2010
DOI: 10.1681/asn.2009121295
|View full text |Cite
|
Sign up to set email alerts
|

SPAK-Knockout Mice Manifest Gitelman Syndrome and Impaired Vasoconstriction

Abstract: Polymorphisms in the gene encoding sterile 20/SPS1-related proline/alanine-rich kinase (SPAK) associate with hypertension susceptibility in humans. SPAK interacts with WNK kinases to regulate the Na ϩ -K ϩ -2Cl Ϫ and NaMutations in WNK1/4 and N(K)CC can cause changes in BP and dyskalemia in humans, but the physiologic role of SPAK in vivo is unknown. We generated and analyzed SPAK-null mice by targeting disruption of exons 9 and 10 of SPAK. Compared with SPAK ϩ/ϩ littermates, SPAK ϩ/Ϫ mice exhibited hypotensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

21
320
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 249 publications
(344 citation statements)
references
References 44 publications
(56 reference statements)
21
320
3
Order By: Relevance
“…Although in sensory neurons the two kinases seem to fulfill a redundant function (12) based on the phenotypes of SPAK and kidney-specific OSR1 knock-out mice, the two kinases in kidney seem to have very distinct roles. Indeed, although the SPAK knock-out mouse reveals a primary role for SPAK in regulating the Na-Cl cotransporter in the distal convoluted tubule (13)(14)(15)(16), the kidney-specific OSR1 knock-out mouse displays a phenotype that is consistent with disruption of NKCC2 function in the TAL (17). An intriguing observation from the SPAK knock-out mouse is that NKCC2 in the TAL is hyperphosphorylated (13,14,16), which would be inconsistent if the kinase was phosphorylating this cotransporter under normal conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although in sensory neurons the two kinases seem to fulfill a redundant function (12) based on the phenotypes of SPAK and kidney-specific OSR1 knock-out mice, the two kinases in kidney seem to have very distinct roles. Indeed, although the SPAK knock-out mouse reveals a primary role for SPAK in regulating the Na-Cl cotransporter in the distal convoluted tubule (13)(14)(15)(16), the kidney-specific OSR1 knock-out mouse displays a phenotype that is consistent with disruption of NKCC2 function in the TAL (17). An intriguing observation from the SPAK knock-out mouse is that NKCC2 in the TAL is hyperphosphorylated (13,14,16), which would be inconsistent if the kinase was phosphorylating this cotransporter under normal conditions.…”
mentioning
confidence: 99%
“…Indeed, although the SPAK knock-out mouse reveals a primary role for SPAK in regulating the Na-Cl cotransporter in the distal convoluted tubule (13)(14)(15)(16), the kidney-specific OSR1 knock-out mouse displays a phenotype that is consistent with disruption of NKCC2 function in the TAL (17). An intriguing observation from the SPAK knock-out mouse is that NKCC2 in the TAL is hyperphosphorylated (13,14,16), which would be inconsistent if the kinase was phosphorylating this cotransporter under normal conditions. In the kidney medulla several smaller SPAK fragments are observed by Western blot analysis, and these fragments have been postulated to act as negative regulators of OSR1 function in the thick ascending limb of Henle (14,16,18).…”
mentioning
confidence: 99%
“…We and other groups have previously shown that the with-nolysine kinase-SPAK-Na-Cl cotransporter/NKCC signaling cascade plays a pivotal role in BP regulation in the kidney and aorta. [17][18][19][20] This study suggests that subjects with rs3754777 develop an activation of this cascade primarily based on increased SPAK transcription, leading to hypertension. A previous study showed a link between genetic variants and saltsensitive BP elevation in Korean population 32 and identified this SNP as one of the variants associated with salt sensitivity.…”
Section: Discussionmentioning
confidence: 75%
“…[17][18][19][20][21] In particular, phosphorylation and activation of the SLC12A cotransporters (Na-Cl cotransporter/Na-K-Cl cotransporter 1/2 [NKCC1/NKCC2]) have been shown to depend completely on SPAK and oxidative stress responsive 1 activity. [18][19][20][21] Thus, STK39 polymorphisms have been speculated to modulate the function of these cotransporters, resulting in BP elevation. 4 However, the biochemical functions of these polymorphisms and the mechanisms of their contribution to hypertension remain to be clarified.…”
Section: December 2015mentioning
confidence: 99%
See 1 more Smart Citation